The chaperone‐like sodium phenylbutyrate improves factor IX intracellular trafficking and activity impaired by the frequent p.R294Q mutation. (9th August 2018) - Pignani, S.; Todaro, A.; Ferrarese, M.; Marchi, S.; Lombardi, S.; Balestra, D.; Pinton, P.; Bernardi, F.; Pinotti, M.; Branchini, A.
Abstract : Essentials Missense mutations often impair protein folding, and thus intracellular trafficking and secretion. Cellular models of severe type I hemophilia B were challenged with chaperone‐like compounds. Sodium phenylbutyrate improved intracellular trafficking and secretion of the frequent p.R294Q. The increased coagulant activity levels (∼3%) of p.R294Q would ameliorate the bleeding phenotype. Summary: Background: Missense mutations often impair protein folding and intracellular processing, which can be improved by small compounds with chaperone‐like activity. However, little has been done in coagulopathies, where even modest increases of functional levels could have therapeutic implications. Objectives: To rescue the expression of factor IX (FIX) variants affected by missense mutations associated with type I hemophilia B (HB) through chaperone‐like compounds. Methods: Expression studies of recombinant (r)FIX variants and evaluation of secreted levels (ELISA), intracellular trafficking (immunofluorescence) and activity (coagulant assays) before and after treatment of cells with chaperone‐like compounds. Results: As a model we chose the most frequent HB mutation (p.R294Q, ~100 patients), compared with other recurrent mutations associated with severe/moderate type I HB. Immunofluorescence studies revealed retention of rFIX variants in the endoplasmic reticulum and negligible localization in the Golgi, thus indicating impaired intracellular trafficking. Consistently, and in agreement with coagulation phenotypes in patients, all missense mutations resulted in impaired secretion (< 1% wild‐type rFIX). Sodium phenylbutyrate (NaPBA) quantitatively improved trafficking to the Golgi and dose dependently promoted secretion (from 0.3 ± 0.1% to 1.5 ± 0.3%) only of the rFIX‐294Q variant. Noticeably, this variant displayed a specific coagulant activity that was higher (~2.0 fold) than that of wild‐type rFIX in all treatment conditions. Importantly, coagulant activity was concurrently increased to levels (3.0 ± 0.9%) that, if achieved in patients, would ameliorate the bleeding phenotype. Conclusions: Altogether, our data detail molecular mechanisms underlying type I HB and candidate NaPBA as affordable 'personalized' therapeutics for patients affected by the highly frequent p.R294Q mutation, and with reduced access to substitutive therapy.